Pesticidal activity of plant extracts as alternatives to synthetic chemical insecticides to fight against Euscelis sp. and for preservation of Apis mellifera Linnaeus associated to the inflorescences of Ocimum basilicum L. - Kosini, Daniel; Adamou, Moïse; Mohammadou, Moukhtar; Yatahaï, Clément Mineo; Ousmana, Youssoufa; Tchoubou-Sale, Abraham; Massah, Odette Dabolé; Oumarou, Abdoul Aziz; Nukenine, Elias Nchiwan (Journal of Plant Protection Research, 2025)
In recent years, researchers have increasingly focused on using secondary compounds from plant extracts as potential alternatives to synthetic insecticides, which can harm biodiversity, including pollinators. This study evaluated the effectiveness of aqueous leaf extracts from Azadirachta indica A. Juss., Carica papaya L. and Calotropis procera (Ait.) R.BR. on the population density of Euscelis sp. and the foraging behavior of Apis mellifera Linnaeus in a basil (Ocimum basilicum L.) field during both the rainy and dry seasons. Trials were carried out using a RCBD with four replications: three plant extracts x one positive control (parastar) x one negative control x four groups of flowers (1: exposed to all pollinators, 2: protected from insects, 3: exposed only to A. mellifera and 4: uncovered without insect visits). Results showed that all botanical extracts exhibited insecticidal effects comparable to parastar against Euscelis sp. Among the 11 pollinator species recorded, A. mellifera was the most frequent visitor, foraging throughout the day with activity peaking at 10–11 AM during the dry season and 12–1 PM during the rainy season. The highest abundance of A. mellifera per 1000 flowers was recorded in the C. papaya treatment, which significantly improved seed yield. These results suggest that the tested botanical extracts are promising eco-friendly alternatives for integrated pest management, helping to reduce the risks of synthetic insecticides to pollinators and enhance basil seed production.